Analisis Determinan Nilai Tukar di Indonesia Selama Periode 2021-2023 - Abigail, Aurelia Mayza; Arintoko, Arintoko; Pravitasari, Chairani Fadhila (Lingka Ekonomika, 2025)
This study analyzes the determinants of the Rupiah exchange rate (EXR) against the US Dollar from 2021 to 2023, focusing on the effects of net exports (EM), inflation (INF), interest rates (INT), and world oil prices (OIL). Using time series data and the ARDL model, the results show that net exports (EM) and world oil prices (OIL) have no significant impact. Inflation (INF) has a negative and significant effect in the long run, while interest rates (INT) have a positive and significant effect in both the short and long run. These findings highlight the importance of inflation control, consistent monetary policy, and energy diversification in maintaining exchange rate stability and macroeconomic resilience.